MiR-608 overexpression in idiopathic pulmonary fibrosis (IPF) - Epstein Shochet, Gali; Israeli-Shani, Lilach; Kains, Isabelle; Wand, Ori; Shitrit, David (BMC pulmonary medicine, 2021)
Background Idiopathic pulmonary fibrosis (IPF) is a chronic progressive disease that causes scarring of the lungs. The disease is associated with the usual interstitial pneumonia pattern, which was not yet fully recapitulated by an animal model. Therefore, the disease is considered ‘human specific’. miRNA-608 is a primate specific miRNA with many potential targets, such CdC42 and Interlukin-6 (IL-6) that were previously implicated in IPF pathology. Objective To test miR-608 expression and its targets in IPF patient samples. Methods RNA was extracted from Formalin fixed paraffin embedded tissue sections (N = 18). miRNA-608 and Cdc42 and IL-6 levels were analyzed by qPCR. Acetylcholinesterase (AChE) is another target of miRNA-608. Its’ rs17228616 allele has a single-nucleotide polymorphism causing weakened miR-608 interaction (C2098A). Thus, DNA was extracted from whole blood samples from 56 subjects with fibrosing interstitial lung disease and this region was sequenced for assessment of rs17228616 allele polymorphism. Results miR-608 is significantly overexpressed in IPF samples in comparison with controls ( p < 0.05). Cdc42 and IL-6 levels were lower in the IPF patient samples compared with control samples ( p < 0.001 and p < 0.05, respectively). The frequency of the rs17228616 minor A-allele was 17/56 (30.4%) with all patients being heterozygous. This result is significant vs. the published Israeli cohort of healthy individuals, which reported 17% prevalence of this allele in healthy control volunteers ( p = 0.01, OR = 2.1, CI 95% [1.19–3.9]). Conclusion miR-608 is overexpressed in IPF patients. While the exact mechanism remains to be discovered, it could potentially promote fibrotic disease.